2015
DOI: 10.1007/s00198-015-3376-7
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of barriers and facilitators to older adults’ participation in higher impact physical activity and bone health: a qualitative study

Abstract: SummaryThis qualitative study explored the acceptability of high-impact physical activity for increasing bone strength in later life. Thematic analysis established the barriers and facilitators to this physical activity. They prioritised joint over skeletal health, of which they had little concept. Interventions need to clearly communicate the rationale and benefits.IntroductionThe aim of this study was to explore the acceptability of doing high-impact physical activity in later life.MethodsThis qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Review of the references of one paper led to the discovery of additional papers on older adults' attitudes to falls prevention programmes, which were included [6][7][8] to present views specific to falls prevention activities. So in total, seventeen papers were included: five systematic reviews 5,7,9,10,11 ; three reviews 6,12,13 ; and nine primary studies for context 8,[14][15][16][17][18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the references of one paper led to the discovery of additional papers on older adults' attitudes to falls prevention programmes, which were included [6][7][8] to present views specific to falls prevention activities. So in total, seventeen papers were included: five systematic reviews 5,7,9,10,11 ; three reviews 6,12,13 ; and nine primary studies for context 8,[14][15][16][17][18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining primary studies [14][15][16][17][18]20,21 were all qualitative studies that set out to explore attitudes towards different types of strength and balance activities. The study participants were mainly people taking part in specific programmes of resistance exercise; falls prevention programmes; bone strength programmes or general activity programmes with a specific component targeting strength.…”
Section: Sense Of Belonging 4 Increase Social Activity 2 Observing Otmentioning
confidence: 99%
“…Motivation is the first step for behavior change. A study aimed at the participation of middle-aged people in high-impact physical activity showed that the perception of clear and tangible benefits acts as a motivator for adherence to the practice of physical activities (23) . Another study, conducted with patients submitted to stem cell transplantation, reported that being part of a physical activity motivation program reduced the hospitalization period, in addition to arousing a sense of commitment to physical activity, even when the participants were tired (24) .…”
Section: Educational Technology For Fatigue Management Related To Antmentioning
confidence: 99%
“…(13) However, in older people without radiographic or symptomatic knee OA, recreational activity did not increase risk of OA development (14) and a review of studies investigating the mid-term to long-term effects of exercise of a range of modes on articular cartilage found no evidence of detrimental effects, (15) although few included high-impact exercise. (13) However, in older people without radiographic or symptomatic knee OA, recreational activity did not increase risk of OA development (14) and a review of studies investigating the mid-term to long-term effects of exercise of a range of modes on articular cartilage found no evidence of detrimental effects, (15) although few included high-impact exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Although high-impact exercise is beneficial to bone strength, older people may have concerns as to the effect on their joints. (13) However, in older people without radiographic or symptomatic knee OA, recreational activity did not increase risk of OA development (14) and a review of studies investigating the mid-term to long-term effects of exercise of a range of modes on articular cartilage found no evidence of detrimental effects, (15) although few included high-impact exercise. High-impact exercise has been shown to improve femoral neck bone mineral content (BMC) with no change in quantitative MRI biomarkers or cartilage composition in postmenopausal women with mild OA, (16) but there is little research using quantitative MRI in those without a diagnosis of OA.…”
Section: Introductionmentioning
confidence: 99%